2016
DOI: 10.3390/ijms17020237
|View full text |Cite
|
Sign up to set email alerts
|

Implications of MicroRNAs in the Treatment of Gefitinib-Resistant Non-Small Cell Lung Cancer

Abstract: Non-small cell lung cancer (NSCLC) represents about 85% of the reported cases of lung cancer. Acquired resistance to targeted therapy with epidermal growth factor receptor-tyrosine kinase inhibitors (EGFR-TKIs), such as gefitinib, is not uncommon. It is thus vital to explore novel strategies to restore sensitivity to gefitinib. Provided that microRNAs (miRNAs) negatively regulate their gene targets at the transcriptional level, it is speculated that miRNA mimetics may reduce the expression, activity and signal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 53 publications
0
34
0
Order By: Relevance
“…MicroRNAs (miRNAs) are a class of endogenous short non-coding RNAs, which can repress gene expression by base pairing to specific recognition sequences in the 3′-untranslated region (UTR) of their target mRNAs [4]. Accumulating evidence has shown that miRNAs are associated with tumourigenesis, progression and metastasis either as oncogenes or tumour suppressors in NPC and other cancers by regulating target gene expression [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a class of endogenous short non-coding RNAs, which can repress gene expression by base pairing to specific recognition sequences in the 3′-untranslated region (UTR) of their target mRNAs [4]. Accumulating evidence has shown that miRNAs are associated with tumourigenesis, progression and metastasis either as oncogenes or tumour suppressors in NPC and other cancers by regulating target gene expression [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the relatively rapid acquisition of resistance to such treatments that is observed in virtually all patients significantly limits their utility and remains a substantial challenge to the clinical management of advanced lung cancers and the further development of targeted therapies. Since molecular mechanisms of resistance have been identified, new strategies to overcome or prevent the development of resistance have emerged, including the regulation of specific signalling pathways by epigenetic mechanisms [9].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this may affect the regulation of the proliferation, apoptosis as well as invasion of tumor cells and other important physiological activities (26). To be specific, the upregulation of PI3K/ AKT/mTOR pathway can promote the proliferation of tumor cells, induce the invasiveness and inhibit apoptosis of tumor cells, and promote tumor growth (27). Therefore, a variety of PI3K/AKT/mTOR pathway inhibitors have been developed.…”
Section: Discussionmentioning
confidence: 99%